Synthesis and characterization of Interpenetrating polymer network microspheres of acryl amide grafted Carboxymethylcellulose and Sodium alginate for controlled release of Triprolidine hydrochloride monohydrate - P. Ramakrishna, K. Madhusudana Rao, K.V. Sekharnath, P. Kumarbabu, S. Veeraprathap, K. Chowdoji Rao, and M.C.S. Subha (Journal of Applied Pharmaceutical Science, 2013)
Interpenetrating polymer network [IPN] microspheres of acrylamide (AAm) grafted on Carboxymethyl cellulose (CMC) and Sodium alginate (NaAlg) microspheres were prepared by water-in-oil (W/O) emulsion method. These microspheres were loaded with Triprolidine hydrochloride monohydrate (TPH) and cross-linked with glutaraldehyde. The prepared microspheres were characterized by Differential scanning calorimetry (DSC), Scanning electron microscopy (SEM) and Laser particle size analyzer. DSC thermo grams of TPH loaded AAm-g-CMC/NaAlg IPN microspheres confirmed the molecular level distribution in the polymer matrix. SEM of the microspheres suggested the formation of spherical particles. Swelling experiments on the microspheres provided important information on drug diffusion properties. Release data have been analyzed using an empirical equation to understand the nature of transport of drug containing solution through the polymeric matrices. The controlled release characteristic of the matrices for TPH was investigated in pH 7.4 media. Particle size and size distribution of the microspheres was studied by laser light diffraction particle size analyzer. Drug was released in a controlled manner upto 12 h.
Keywords: Graft polymer, semi IPN, microspheres, triprolidine